PREVALENSI FILARIASIS DAN GAMBARAN PENGOBATAN MASAL DI WILAYAH KERJA PUSKESMAS JEMBATAN MAS KABUPATEN BATANG HARI - Arini Arini; Lintang Dian Saraswati; Praba Ginandjar; Martini Martini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
In 2011, Batang Hari Districts had a microfilaria rate of 1.5% and has performed filariasis MDA for 5 consecutive years from 2012 to 2016. This study aimed to calculate the prevalence of filariasis and mass drug description of the occurrence of fiariasis in the work area of Puskesmas Jembatan Mas 2017. This was a descriptive study. Study population was people who got MDA in 2015 in Puskesmas Jembatan Mas consist of 13,819 people, samples were 100 respondents. Sampling technique using proportional random sampling. By 2017, the results of this study show that the coverage of people taking filariasis prevention drugs is 60%. Characteristics of respondents in the form of age, sex, occupation, education, knowledge POPM filariasis, and the practice of taking medicine. Based on adherence level of non-adherence medication, based on age group 60-69 years (50.0%), male gender (44.2%), did not complete primary school (68.4%), civil servant (85,7%), whereas poor filariasis knowledge did not adhere to taking medication (45.5%), poor POPM knowledge did not adhere to medication (47.7%), and TPE support did not adhere to taking medication (65.4%). Therefore the need to inform the public to quickly respond to the information given either in the form of counseling, information and electronic newspapers, and banners and posters. It is expected that every community filariasis POPM complies with taking filariasis prevention drugs.